ANALISIS STATUS KESUBURAN TANAH PADA LAHAN BUDIDAYA RUMPUT ODOT (Pennisetum purpureum CV. MOOT) DENGAN PERLAKUAN PUPUK BOKASHI SLUDGE BIOGAS BERBEDA - Marten Umbu Nganji; I Made Adi Sudarma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The process of cultivating odot grass by some breeders is still conventional through simple land management and has not used appropriate fertilization technology, both inorganic and organic fertilizers. In this study, organic matter in the form of bokashi sludge biogas fertilizer was used as a basal fertilizer for use in the cultivation of odot grass. Soil samples collected from Kawangu Village, Pandawai District, East Sumba Regency, were analyzed at the Laboratory of Nusa Cendana University, Kupang. Soil sampling was carried out in a composite manner on plots of land to be planted with odot grass with an area of ​​2 x 1 m where 20 plots of land had been made. The plots of land were treated with a mixture of different bokashi sludge biogas fertilizers in soil media with each treatment, namely without bokashi fertilizer, 10 t ha-1 biogas bokashi sludge fertilizer, 20 t ha-1 biogas bokashi sludge fertilizer, 30 t ha-1 biogas bokashi sludge fertilizer, 40 t ha-1 biogas bokashi sludge fertilizer. The results of the combined criteria for soil chemical properties showed that the status of soil fertility in odot grass cultivation without bokashi sludge biogas fertilizer was in the medium soil fertility category, while the treatments with bokashi sludge biogas fertilizers of 10 t ha-1, 20 t ha-1, 30 t ha-1, and 40 t ha-1 were at high soil fertility levels.